AKTIVITAS ANTIOKSIDAN PADA EKSTRAK DAUN, RANTING, DAN KULIT BUAH JERUK PURUT (Citrus hystrix DC.) DENGAN METODE 2,2-DIFENIL-1- PIKRILHIDRAZIL (DPPH) dan CUPRIC REDUCING ANTIOXIDANT ACTIVITY (CUPRAC) - Johan, Yurika
Makrut lime is a plant that has been known to Indonesian people. However, the utilization of the makrut lime is still not optimal. Based on recent research, makrut lime contained phenolic compounds, flavonoids, and carotenoids which have antioxidant activity. The objectives of this research were to study antioxidant activity of various extracts from leaves, twig, and peels of makrut lime (Citrus hystrix DC.) using two methods of antioxidant assays which were IC50 DPPH and EC50 CUPRAC assays, to determine total phenolic, flavonoid, and carotenoid of each extract, to analyze the correlation of total phenolic, flavonoid, and carotenoid to IC50 DPPH and EC50 CUPRAC assays, and to determine correlation between the two method of antioxidant IC50 DPPH and EC50 CUPRAC assays. Extraction was performed by reflux using three diferent polarities of solvents, n-hexane, ethyl acetate, and ethanol, respectively. Extracts were monitored by thin layer chromatography (TLC). Antioxidant activity of each extract was tested using DPPH and CUPRAC assays to determine of IC50 of DPPH, EC50 of CUPRAC, determination of total phenols, flavonoid, and carotenoid content were performed by spectrophotometry UV-Vis. Correlation between total phenolic, flavonoid, carotenoid, IC50 DPPH, EC50 CUPRAC, and correlation between IC50 DPPH and EC50 CUPRAC were analyzed by Pearson method. The highest antioxidant activity with IC50 DPPH (0.63 µg/mL) and EC50 CUPRAC (123 µg/mL) was given by ethyl acetate twig extract of makrut lime. Ethyl acetate twig extract of makrut lime had the highest total phenolic (8.35 g GAE/ 100 g) and the highest total carotenoid (1.81 g BE/100 g). N-hexane twig extract of makrut lime had the highest total flavonoid (8.69 g QE/ 100 g). Total phenols in peels and twig extracts of makrut lime had highly negative and significant correlation with IC50 of DPPH (peels, r = -0.89 p <0.01; twig, r = -0.99 p < 0.01). Total flavonoid in leaves, peels, and twig extracts of makrut lime had highly negative and significant correlation with EC50 of CUPRAC (leaves, r = -0.93 p < 0.01; peels, r = -0.97 p < 0.01; twig, r = -0.94 p < 0.01). Total carotenoid in leaves, peels, and twig extracts of makrut lime had highly negative and significant correlation with EC50 of CUPRAC (leaves, r = -0.99 p < 0.01; peels, r = -0.85 p < 0.01; twig, r = - 0.83 p < 0.01). All of leaves, peels, and twig extract of makrut lime (except n-hexane peels extract) were very strong antioxidant by DPPH method. Phenolic compounds in peels and twig extract of makrut lime were the major contributor in the IC50 of DPPH. IC50 of DPPH of peels and twig extracts of makrut lime could be estimated indirectly by determining total phenolic content. Flavonoid and carotenoid in leaves, peels, and twig extracts of makrut lime were the major contributor in the EC50 of CUPRAC. EC50 of CUPRAC capacity of leaves, peels and twig extracts could be indirectly estimated by determining total flavonoid and carotenoid content. IC50 DPPH of leaves, peels, and twig extracts of makrut lime had no linear result with their EC50 CUPRAC. There were no correlation between IC50 of DPPH and EC50 of CUPRAC of all the extracts, therefore IC50 of DPPH cannot be predicted by EC50 of CUPRAC.